CLINIC, DIFFERENTIAL DIAGNOSIS AND TREATMENT OF GALACTOSEMIA - N.V. Zhurkova; O.B. Kondakova; T.V. Bushueva; E.P. Rybakova; T.E. Borovik ("Paediatrician" Publishers LLC, 2008)
The data of different firms of hereditary galactosemia was analyzed in this article. Clinical and biochemical characteristics and molecular and genetic features of diagnostics of this disease were described. The information about differential diagnosis and problems, related with hereditary galactozemia screening in Russia was given.Key words: children, galactosemia, treatment, screening.